Workhorse : my sublime and absurd years in New York City's restaurant scene - Reed, Kim, 1978- (Hachette Books, 2021)
"For years, Kim's day job was a social worker to the home-bound elderly in Brooklyn Heights. Then she'd scramble into Manhattan to make her hostess shifts at Babbo, where even the Pope would have trouble scoring a reservation, and Gwyneth Paltrow and Ryan Reynolds squeezed through the jam-packed entryway like everyone else. Despite her sometimes fifteen-hour days, Kim couldn't make ends meet, up to her eyeballs in grad school debt. Her social work training -- problem solving, crisis intervention work, dealing with unpredictable people and random situations -- made her the ideal assistant for Joe Bastianich, a hard-partying, "What's next?" food and wine entrepreneur who drummed up new business ventures one after another. He rose to fame in Italy as a TV star while Kim planned parties, fielded calls, and negotiated his deals from a cell phone on the go. Eventually, something had to give, and that was Kim herself. With no life outside her job, she was panicked about ending up alone without building the family she craved. Workhorse is a deep-dive into the chaos of the NYC foodie craze as well as an all-too-relatable look at what happens when your job takes over your life, and when a scandal upends your understanding of where you work and what you do. As Kim realized, if you can make the impossible possible for someone else, you can do the same for yourself"--